The Influence of Attractiveness and the Content of the News Message on the Handling of Covid-19 on the Public's Perception of the Sukabumi City Government - Muhammad Tanziil Suherman; Itsna Nurhayat E (Budapest International Research and Critics University, 2022)
This research is entitled The influence of attractiveness and the content of the news message on the handling of Covid-19 on the public's perception of the Sukabumi City Government. This study uses quantitative methods with path analysis. The purpose of this study was to determine the magnitude of the influence of the attractiveness factor and the content of the news message on the handling of Covid-19 on the public's perception of the Sukabumi City Government. The results of this study indicate that the attractiveness and message content variables have a significant effect on the perception variable. The conclusion of this study shows that the attractiveness factor and the content of the news message have a significant effect on the Y variable, namely perception. That by giving an appeal to the news and the content of the message that is conveyed continuously, the attractiveness and content of the news message will affect the perception of the audience who reads or watches the show.